Therapeutic applications of digital interventions for adhd: analysis of clinical evidence - Antypenko, L.; Antypenko, O. M.; Антипенко, Олексій Миколайович (My University, 2025)
This systematic review examines digital therapeutic interventions for attention-deficit/hyperactivity disorder (ADHD) across 12 clinical trials. Results demonstrate modest, but significant improvements in attention, cognitive performance, and symptom reduction, particularly with multimodal approaches. Despite methodological variability, findings consistently support digital therapeutics as promising complementary approaches for ADHD management, with multimodal interventions showing particular efficacy.
Keywords: ADHD; digital therapeutics; cognitive training; neurodevelopmental disorders; digital health interventions